Cross-language perception of non-native stops and fricatives among Malay and Hausa native speakers - Abdullahi, Jamilu; Yap, Ngee Thai; Md Rashid, Sabariah; Hossein, Vahid Nimehchisalem (Universiti Putra Malaysia Press, 2019)
This study examines the effect of native language on listeners' perception of native and non-native consonants. The study focuses on cross-language perception of selected stops and fricatives among Hausa speakers who have little exposure to Malay, and Malay speakers who have no exposure to Hausa. The primary goal of this study is to examine how Hausa and Malay speakers perceived non-native stops and fricatives that are absent in their native language. Hausa language has a combination of plosives and implosives which involves the use of different airstream mechanisms in their production. Malay speakers who do not have any experience of implosives may find it difficult to discriminate between implosives and plosives, and to produce implosives accurately. In contrast, Hausa speakers may have difficulty discriminating between labial stops and fricatives in Malay as this distinction is not present in Hausa. Forty-five Hausa native speakers and forty-five Malay native speakers were recruited for the study. Audio-recording of minimal pairs of Malay and Hausa words were used as stimuli in an AX discrimination task. Subjects had to indicate whether they heard two different words, or the same words presented twice by two different speakers. The results of the study show that the Malay and Hausa native speakers faced considerable difficulties and problems in perceiving most non-native sound contrasts. Native language influence was found to be a major factor influencing the perception of non-native sound contrasts. This study concluded that the Perception Assimilation Model was successful in the prediction and interpretation of most of the perceptual difficulties encountered by the Malay and Hausa native speakers in the perception of stops and fricatives.